Enhancing LoRaWAN Security: Addressing Static Root Keys with Post-Quantum Cryptography - Saldanha, Matheus de O.; Giron, Alexandre A.; Custódio, Ricardo; Idalino, Thaís B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2025)
The lack of an update method for LoRaWAN’s static root keys poses a major security risk, exposing networks to key compromise. Furthermore, existing approaches that use public-key cryptography are vulnerable to emerging quantum threats. This paper presents a quantum-safe solution to dynamically update root keys through a Root Key Renewal procedure, using post-quantum authenticated Diffie–Hellman via CSIDH and post-quantum signatures. To avoid a similar stagnation of the new signature key pairs, a Key Pair Update procedure is also proposed to refresh them. The proposed solution is tested in a simulated setup and the results show that HAWK, SNOVA, MAYO, Falcon, and SQISign are viable candidates for post-quantum LoRaWAN deployments.